2011
DOI: 10.1542/peds.2010-1722p
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Perceived Credibility of Vaccine-Safety Information for Parents

Abstract: CONTEXT: The source of health information can have an impact on the manner and frequency of its use. In the arena of vaccine safety, a variety of sources promulgate information from very different perspectives. The spectrum runs from traditional sources such as public health officials and physicians to nontraditional sources, such as celebrities. OBJECTIVE:To assess what proportion of parents trust vaccine information from different sources and whether different groups of parents vary in their trust of such in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
207
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 320 publications
(236 citation statements)
references
References 12 publications
18
207
1
3
Order By: Relevance
“…Importantly, this survey was conducted at a single point in time in a rapidly changing landscape of online access and usage. The participation rate is consistent with that of other published NPCH-based studies, [22][23][24][25][26] but in survey research, there is always the potential for unmeasured sources of participation bias that may have affected our findings. We attempted to mitigate such bias by providing an invitation that did not mention the subject matter.…”
Section: -33supporting
confidence: 88%
See 2 more Smart Citations
“…Importantly, this survey was conducted at a single point in time in a rapidly changing landscape of online access and usage. The participation rate is consistent with that of other published NPCH-based studies, [22][23][24][25][26] but in survey research, there is always the potential for unmeasured sources of participation bias that may have affected our findings. We attempted to mitigate such bias by providing an invitation that did not mention the subject matter.…”
Section: -33supporting
confidence: 88%
“…When all parents (including those who had never left ratings or comments) were asked to consider the implications of leaving a negative comment about a physician, 34% (95% CI: 31-37) had concerns about their identity being disclosed, and 23% (95% CI: [21][22][23][24][25][26] were concerned about the physician taking action against them. Thirty percent (95% CI: 24-36) of parents who had gone online to seek physician ratings reported having selected a physician for their children based on positive ratings or reviews on a Web site, and another 30% (95% CI: 24-36) reported that they had avoided a physician due to negative ratings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Therefore, preparing individual health care providers to educate parents and confidently combat misconceptions is a cornerstone to increasing trust in vaccine systems. 21,23 Maintaining Active Demand in India…”
Section: Applying These Motivators To the United Statesmentioning
confidence: 99%
“…Research clearly shows that the most convincing proponent for vaccines is the health care provider. [17][18][19] Having to describe the contagion of each individual vaccine-preventable disease would be extremely complex for medical providers, and could undermine communication leading to greater parental confusion with reduced vaccine uptake. Third, selective elimination of nonmedical exemptions could erode herd immunity for other infections if overall vaccine rates are reduced.…”
mentioning
confidence: 99%